Towards a data‐driven approach to scenario generation for serious games. (19th May 2014) - Luo, Linbo; Yin, Haiyan; Cai, Wentong; Lees, Michael; Othman, Nasri Bin; Zhou,; Suiping
ABSTRACT Serious games have recently shown great potential to be adopted in many applications, such as training and education. However, one critical challenge in developing serious games is the authoring of a large set of scenarios for different training objectives. In this paper, we propose a data‐driven approach to automatically generate scenarios for serious games. Compared with other scenario generation methods, our approach leverages on the simulated player performance data to construct the scenario evaluation function for scenario generation. To collect the player performance data, an artificial intelligence (AI) player model is designed to imitate how a human player behaves when playing scenarios. The AI players are used to replace human players for data collection. The experiment results show that our data‐driven approach provides good prediction accuracy on scenario's training intensities. It also outperforms our previous heuristic‐based approach in its capability of generating scenarios that match closer to specified target player performance.Copyright © 2014 John Wiley & Sons, Ltd.